Stitching the 24-hour city life, labor, and the problem of speed in Seoul - Park, Seo Young, 1979- (Cornell University Press, 2021)
"This book examines the meanings and politics of work in one of the world's most vibrant and dynamic global urban marketplaces. A focal point of fervent uprisings against oppressive working conditions in the 1970s and 1980s, Dongdaemun is now an exciting, fast-paced market where international and domestic consumers mingle with tourists against a backdrop of K-pop music and live entertainment, while garment workers zoom about their business at all hours of the day and night. Seo Young Park's ethnography brings readers into close contact with the people who create this hyperkinetic space"